Kajian Tingkat Kesejahteraan Pewalet di Kecamatan Duampanua Kabupaten Pinrang - Fadillah, Nurul; Zhiddiq, Sulaiman; Abbas, Ibrahim (LaGeografia, 2019)
The purpose of this study is what is the level of income concerned has a positive impact on the level of welfare of their household. the population in this study were 117 owner of swallowÂ  in District Duampanua all of swallow owners are drawn into the research sample.this study uses quantitative and qualitative of data. Data collection is done by observation, interviews, questionnaires and documentation techniques.The analysis techniques of data use quantitative and qualitative approaches. From the results of the research, the high category of swallow owners' welfare, namely health and nutrition, the level and pattern of consumption, housing and the environment while including the category of population, education, social and other employment. the results of the analysis show that the number of swallow owners who are included in the high level of welfare is 3 respondent. The results of the analysis show that the number of swallow owners who are included in the high level of welfare is 3 respondent.